2014
DOI: 10.1007/s10529-014-1546-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased fatty acid unsaturation and production of arachidonic acid by homologous over-expression of the mitochondrial malic enzyme in Mortierella alpina

Abstract: Malic enzyme (ME) catalyses the oxidative decarboxylation of L-malate to pyruvate and provides NADPH for intracellular metabolism, such as fatty acid synthesis. Here, the mitochondrial ME (mME) gene from Mortierella alpina was homologously over-expressed. Compared with controls, fungal arachidonic acid (ARA; 20:4 n-6) content increased by 60 % without affecting the total fatty acid content. Our results suggest that enhancing mME activity may be an effective mean to increase industrial production of ARA in M. a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
45
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 18 publications
2
45
0
Order By: Relevance
“…Previous studies reported that M. alpina had low levels of ALA, SDA, and EPA ( 19 ), and expressed no delta 9 elongase ( Fig. 1 ), as previously demonstrated by M. alpina genome determination ( 18 ).…”
supporting
confidence: 78%
See 1 more Smart Citation
“…Previous studies reported that M. alpina had low levels of ALA, SDA, and EPA ( 19 ), and expressed no delta 9 elongase ( Fig. 1 ), as previously demonstrated by M. alpina genome determination ( 18 ).…”
supporting
confidence: 78%
“…Although M. alpina has a disproportionate ratio of -6 to -3 PUFAs ( 19 ), that does not necessarily mean that its FADS6 (MaFADS6) has substrate preference for LA. Previous studies reported that M. alpina had low levels of ALA, SDA, and EPA ( 19 ), and expressed no delta 9 elongase ( Fig.…”
mentioning
confidence: 99%
“…Agrobacterium tumefaciens C58C1 was cultured in YEP medium, which consists of 10 g/liter tryptone, 10 g/liter yeast extract, and 5 g/liter NaCl. The compositions of synthetic complete (SC) medium, minimal medium (MM), and induction medium (IM) were described previously (8,14,15).…”
Section: Methodsmentioning
confidence: 99%
“…NADPH also plays an important role during fatty acid desaturation, which could be significantly improved by overexpressing a mitochondrial ME2 in Mortierella alpina (8) and Mucor circinelloides (9). These results implied that NADPH generated by cytosolic and membrane-bound enzymes may affect fatty acid synthesis and desaturation, respectively.…”
mentioning
confidence: 89%
See 1 more Smart Citation